Қазіргі араб әдебиетірдегі ғылыми фантастика. Science fiction in modern Arabic literature - Aubakirova, K. K. (Journal of Oriental Studies, 2016)
The article considers with the role and ways of development of Science-fiction in modern Arabic literature as a independent kind of genre.